A methods engineering study on Metatek Philippines, Inc. - Causapin, Mark Gabriel (College of Engineering, 2000)
Metatek Philippines Incorporated is one of the fastest growing firms in the Laguna area. It was created to provide powder coating services for Ergonomics Systems Philippines. Only in its second year, the firm has penetrated the outside market by manufacturing filing cabinets of various types. The company had successeful transactions with big corporation such as Coca-Cola Bottlers, PLDT Company, Mitsubishi Motors, and Pepsi Company. The task of improving its production system was a challenge for the group. Applying Methods Engineering techniques was found to be more difficult on field compared to the laboratory setting. Starting the study, the production process was observed and analyzed until significant problems were found. Cause problems were identified using the streamline diagnostic chart. Major problems found were the company's lack of a forecasting system, lack of space for the raw materials and the finished products, delivery delays, workers' safety concerns and quality control. Minor problems include the need for a drinking fountain, additional restrooms, the absence of a guide for the new workers and the leaking coolant for the spot welding equipment. Plant visits, brainstorming and interviews with the workers and the management were conducted until the group came up with the best solutions regarding the problems. Most of the problems found had limited alternatives, so evaluating these were not complicated. Although the benefits of each option were recognized, the primary difficulty encountered was the determination of the costs of their implementation. This would have been vital in the choices of the researchers. However, since there were only few alternatives, conclusions were easily reached. Recommendations were made based on the analyzed alternatives. The basic and important problem defined by the group were given appropriate solutions. Nevertheless, it also recognized the need for further improvement and change. At the last part of the paper, topics for further studies are presented for other work study teams to analyze. These points, though important to the company, are beyond the scope of this course.